2017
DOI: 10.7759/cureus.1465
|View full text |Cite
|
Sign up to set email alerts
|

Not a Common Rectosigmoid Perforation

Abstract: Gastrointestinal perforation is a common complication arising due to homicidal injuries, trauma or intake of medications like aspirin. Intestinal perforation caused by chronic intake of mud, clay or soil is a rare phenomenon and very few cases have been reported in the literature. We hereby present the first case of rectosigmoid perforation from Pakistan which was caused by chronic mud intake in a female patient. Diagnosis of this condition in its early stage is important because it can be fatal if not address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…There are also obvious health risks in the consumption of soil, in particular, ingestion of helminth eggs, such as Ascaris and hookworm. Severe constipation and colon rupture have also been reported with clay consumption [ 8 ]. One study examined the effects of kaolin ingestion on pregnant rats and their fetal development.…”
Section: Discussionmentioning
confidence: 99%
“…There are also obvious health risks in the consumption of soil, in particular, ingestion of helminth eggs, such as Ascaris and hookworm. Severe constipation and colon rupture have also been reported with clay consumption [ 8 ]. One study examined the effects of kaolin ingestion on pregnant rats and their fetal development.…”
Section: Discussionmentioning
confidence: 99%
“…Pica often goes undiagnosed in Pakistan and most of the research available here is on institutionalized population, in the form of case studies which makes it difficult to estimate the global prevalence rates. The case studies reported pica as a factor associated with pregnancy and helminthic infestations in children from low socioeconomic backgrounds [ 26 , 27 , 28 ]. However, while these studies identify the presence of pica but it is not studied as a primary condition in these studies.…”
Section: Introductionmentioning
confidence: 99%